Early and Late Infections in Newborns: Where Do We Stand? A Review - Francesca Cortese; Pietro Scicchitano; Michele Gesualdo; Antonella Filaninno; Elsa De Giorgi; Federico Schettini; Nicola Laforgia; Marco Matteo Ciccone (Elsevier, 2016)
Neonatal sepsis still represents an important cause of mortality and morbidity among infants. According to the onset, we can distinguish "early onset sepsis" when microbiological cultures positive for external pathogens come from newborns during the first 7 days of life (maternal intrapartum transmission); "late onset sepsis" when microbiological cultures positive for external pathogens come from newborns after the first 7 days from delivery (postnatal acquisition). In this review we synthesize the incidence, risk factors, clinical manifestations, and methods of diagnosis and treatment of each type of neonatal infection, in order to better define such a pathological condition which is of great importance in common clinical practice.